2016
DOI: 10.1093/imrn/rnw066
|View full text |Cite
|
Sign up to set email alerts
|

The Degree of the Dormant Operatic Locus

Abstract: Let X be a smooth, projective curve of genus g ≥ 2 over an algebraically closed field of characteristic p > 0. I provide a conjectural formula for the degree of the scheme of dormant PGL(r)-opers on X where r ≥ 2 (I assume that p is greater than an explicit constant depending on g, r). For r = 2 a dormant PGL(2)-oper is a dormant indigenous bundle on X in the sense of Shinichi Mochuzki (and his work provides a formula only for g = 2, r = 2, p ≥ 5, from a different point of view). In 2014, Yasuhiro Wakabayashi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…The former assertion is a direct consequence of Lemma 3.11.3 described below. The latter assertion follows from the former assertion, (26), and Proposition 3.10.5.…”
Section: Denote Bymentioning
confidence: 70%
See 3 more Smart Citations
“…The former assertion is a direct consequence of Lemma 3.11.3 described below. The latter assertion follows from the former assertion, (26), and Proposition 3.10.5.…”
Section: Denote Bymentioning
confidence: 70%
“…2 )-structures on a general smooth proper curve; this is a generalization of Joshi's conjecture (cf. [26,Conjecture 8.1]) for the rank 2 case, which was proved in [51].…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…If r = p, then F X * (L ) is a maximally Frobenius destabilised rank-p stable vector bundle for any line bundle L on an arbitrary smooth projective curve X of genus g ≥ 2 in characteristic p > 0 (see [5] and [11]). If r < p, Zhao [11,Proposition 2.14] showed that for any given natural numbers p > 0, g ≥ 2 and r > 0 with r < p and p g − 1, there exists some maximally Frobenius destabilised rank-r stable vector bundle over some smooth projective curve of genus g ≥ 2 in characteristic p. Under the assumption p > r(r − 1)(r − 2)(g − 1), Joshi and Pauly [3] gave a correspondence between maximally Frobenius destabilised L. Li [2] stable vector bundles of degree 0 and dormant operatic loci, and proved the existence of Frobenius destabilised stable vector bundles of rank r and degree 0. Further results about Frobenius destabilised stable vector bundles can be found in [4,6,7] and [8].…”
Section: Introductionmentioning
confidence: 99%